Modeling the quality of tax audit based on the acceptance of legal taxpayers in business - Mohsen Hajibabaei; Sina Kheradyar; Mojtaba Malekichoobari (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of the current research is to find a model of the quality of tax audit based on the acceptance of legal taxpayers in business. According to its purpose, the research method is applicable; and in terms of implementation, it is qualitative; and has an inductive and comparative approach and a survey strategy. The statistical population of the research consists of 12 financial managers chosen for the sample selection by non-probability judgmental (targeted) sampling method, and the sampling process continued until theoretical saturation was reached. Data collection is done through semi-structured interviews. Data analysis was done using the theme analysis method and paradigm model, through codings and MAXQDA20 software. The findings of the research show the effectiveness of seven dimensions: causative factors including legal issues, taxpayers' issues, issues related to the case, and organizational issues; central factors including acceptance of legal taxpayers; intervening factors including conditions of legal taxpayers, performance of beneficiary organizations, cultural conditions, and infrastructures; background factors including organizational issues, skills of agents, and audit system; consequential factors including maintaining interests, improving attitudes, and increasing income. Extended Abstract Introduction In today's world, tax audit and acceptance of legal taxpayers can face various challenges and issues. This depends on various factors such as tax laws and regulations, audit criteria, tax technology and the role and influence of legal taxpayers in the economy and audit. Changes in tax laws and regulations have had a great impact on tax audits (Shim et al. 2024). Changes in laws may lead to changes in the goals of legal taxpayers, which require new tax adjustments that the auditor must review. Tax audit criteria have a great impact on audit quality (Brezina et al, 2022). The auditor must be sure that he has followed all the auditing principles and standards in order to guarantee the validity and accuracy of taxpayer's financial reports. The use of technology in tax auditing can help improve the quality and efficiency of this process and tax tools based on artificial intelligence and data analysis to obtain more information about the taxes of legal taxpayers and make a more accurate assessment (Asnawi, 2016). The role and influence of legal taxpayers in economics and auditing is very important. Auditors should examine the effects of legal taxpayers on their financial structure and tax performance in order to ensure that the financial reports of legal taxpayers are accurate and reliable (Hofmann et al, 2008). The problems of tax audit quality are of its basic issues; the acceptance of legal taxpayers. When a tax auditor accepts a company or organization as a legal taxpayer, he may face problems. The first problem that may arise is the conflict of interest. The auditor may be involved in a conflict of interest between the taxpayer's tax objectives and his audit duties (Francis, 2004). This factor leads to a decrease in the quality of the audit and public trust in the audit report. The inefficiency in conducting the audit is possible to be due to conflict of interests or other conditions, thus the auditor may not be able to conduct a detailed and efficient audit and correctly identify tax deficiencies or related laws (Vierra Gracia Dharmawan, 2019). Therefore, in this research, we are looking for an answer to this question: what is the pattern of tax audit quality based on the acceptance of legal taxpayers in business? Theoretical Framework Tax audit Tax audit is an important audit process carried out by professional auditors. The main purpose of this type of audit is to evaluate and confirm the correctness of accounts, financial reports and tax related documents. Tax audit includes the detailed examination of tax documents, tax calculations, compliance with tax laws and regulations and their strict application in order to ensure correct and legal compliance with tax regulations. In tax audit, auditors must have sufficient expertise and experience in the field of taxation to be able to make accurate and correct assessments (Modugu & Anyaduba, 2014). Tax audit quality Tax audit is an audit process whose purpose is to evaluate and verify the correctness of accounts and financial reports related to tax. This assessment includes the review and assessment of tax documents, tax calculations, application of tax regulations and their compliance with relevant tax laws and regulations. The quality of tax audit is very important, because mistakes or defects in tax audit may lead to payment of additional tax or tax penalties (Nugrahanto & Alhadi, 2021). Legal taxpayers Legal taxpayers refer to legal entities that pay VAT for the products and services they purchase. These persons may be producers, suppliers, retailers or other legal entities involved in the process of production and distribution of products and services (Rostami, 2008). The tax audit quality based on the legal taxpayers' acceptance The quality of tax audit based on the acceptance of legal taxpayers means improving the performance and efficiency of the tax audit performed by auditors. This approach means that auditors should carefully examine their legal taxpayers and ensure that their financial and tax information is correct and complete (Nugrahanto & Alhadi, 2021). Delbari Ragheb & Ismailzadeh (2023) conducted a research called the independent audit quality model with an emphasis on meeting the needs of stakeholders. They showed that the multifaceted research model includes four common components and three classifications; the components of the research model have an interactive relationship with each other; this relationship creates a situation where each component of the model is placed in the conditions of influence and effectiveness with respect to the other component; this model while confirming the ethical theory of auditing, shows the view and mental image of the interviewees of the research on the quality of independent auditing with emphasis on the satisfaction of the needs of the beneficiaries. Jamshidi et al, (2023) investigated the explanation and validation of effective factors in the tax audit quality improvement model. The findings of the research showed that the causal factors affecting the improvement of the tax audit quality model have a positive and significant effect on the central phenomenon categories affecting the improvement of the tax audit quality model. Also, the findings showed that the categories of central phenomenon, background factors and intervening factors affecting the improvement of the tax audit quality model have a positive and significant effect on the strategic factors affecting the improvement of the tax audit quality model. Also, the findings showed that strategic factors have a positive and significant effect on the results. Research methodology The research method is applicable in terms of purpose, qualitative in terms of implementation, and has an inductive and comparative approach and a survey strategy. The statistical population of the research consists of 12 financial managers chosen for the sample selection by non-probability judgmental (targeted) sampling method, and the sampling process continued until theoretical saturation was reached. Data collection is done through semi-structured interviews. Data analysis was done using the theme analysis method and paradigm model, through codings and MAXQDA20 software. Research findings The findings of the research show the effectiveness of seven dimensions: causative factors including legal issues, taxpayers' issues, issues related to the case, and organizational issues; central factors including acceptance of legal taxpayers; intervening factors including conditions of legal taxpayers, performance of beneficiary organizations, cultural conditions, and infrastructures; background factors including organizational issues, skills of agents, and audit system; consequential factors including maintaining interests, improving attitudes, and increasing income. Conclusion The current research was conducted with the aim of modeling the quality of tax audits based on the acceptance of legal taxpayers in business. The results of this research are in agreement with the results of Kai et al, (2023), Seckler et al, (2023), Delbari Ragheb & Ismailzadeh (2023), Hassanjani Khoshkroudi et al, (2023), Najibzadeh & Mirbagheri Heer (2023), Jamshidi et al, (2023), Ahmadi & Azmoun (2023), Dast Akhiz & Asadi (2023), and Ghashghai & Khaligh (2022). Jamshidi et al, (2023) investigated the explanation and validation of effective factors in the tax audit quality improvement model. The findings of the research showed that the causal factors affecting the improvement of the tax audit quality model have a positive and significant effect on the central phenomenon categories affecting the improvement of the tax audit quality model. Also, the findings showed that the categories of central phenomenon, background factors and intervening factors affecting the improvement of the tax audit quality model have a positive and significant effect on the strategic factors affecting the improvement of the tax audit quality model. Also, the findings showed that strategic factors have a positive and significant effect on the results. According to the results of this research, the following suggestions are presented: The quality of tax audit based on the acceptance of legal taxpayers in business is very important. Considering the legal issues, the skills of the agents, and the audit system, this issue plays a very important role in the performance of the beneficiary organizations. The conditions of legal taxpayers and the online system also play an important role in this matter. In order to improve the attitude and increase income, it is necessary for the beneficiary organizations to improve the tax audit system based on the acceptance of legal taxpayers. This preserves interests and improves public attitudes towards organizations.